Analisa Kinerja Algoritma C.45 Dalam Memprediksi Hasil Belajar - Muhammad Ardiansyah Sembiring; Mustika Fitri Larasati Sibuea; Andy Sapta (Smart Education, 2018)
This research was done to predict the cumulative achievement index of students STMIK Royal Kisaran is based on students' academic history at the time of senior high school. This research will inform the student for early anticipation in following the lecture in order to get the maximum learning. The method used in solving this problem is by the method Decission tree C.45 algorithm starts from the formation of the decision system as preliminary data have attribute values and decision condition. Then calculate the entropy of each attribute. Calculating the highest gain value which would then be used as nodes. Determining Following the decision of the result tree Decission process using if-then logic begins from the highest to the root of the lowest roots. This research resulted in 7 pieces of pattern rules (rule) as a basis for predicting student achievement of learning outcomes. Keywords: data mining, algorithm C.45, learning Outcomes.